Progressive Degenerative Myopathy and Myosteatosis in ASNSD1-Deficient Mice. Issue 5 (September 2020) - Vogel, Peter; Ding, Zhi-Ming; Read, Robert; DaCosta, Christopher M.; Hansard, Melissa; Small, Daniel L.; Ye, Gui-lan; Hansen, Gwenn; Brommage, Robert; Powell, David R.
Mice with an inactivating mutation in the gene encoding asparagine synthetase domain containing 1 (ASNSD1) develop a progressive degenerative myopathy that results in severe sarcopenia and myosteatosis. ASNSD1 is conserved across many species, and whole body gene expression surveys show maximal expression levels of ASNSD1 in skeletal muscle. However, potential functions of this protein have not been previously reported. Asnsd1 −/− mice demonstrated severe muscle weakness, and their normalized body fat percentage on both normal chow and high fat diets was greater than 2 SD above the mean for 3651 chow-fed and 2463 high-fat-diet–fed knockout (KO) lines tested. Histologic lesions were essentially limited to the muscle and were characterized by a progressive degenerative myopathy with extensive transdifferentiation and replacement of muscle by well-differentiated adipose tissue. There was minimal inflammation, fibrosis, and muscle regeneration associated with this myopathy. In addition, the absence of any signs of lipotoxicity in Asnsd1 −/− mice despite their extremely elevated body fat percentage and low muscle mass suggests a role for metabolic dysfunctions in the development of this phenotype. Asnsd1 −/− mice provide the first insight into the function of this protein, and this mouse model could prove useful in elucidating fundamental metabolic interactions between skeletal muscle and adipose tissue.